Supramolecular Carbon Monoxide‐Releasing Peptide Hydrogel Patch. (25th September 2018) - Kim, Inhye; Han, Eun Hee; Bang, Woo‐Young; Ryu, Jooyeon; Min, Jin‐Young; Nam, Hyeong Chan; Park, Won Ho; Chung, Young‐Ho; Lee, Eunji
Abstract: Carbon monoxide (CO) is recently accepted as a therapeutic molecule that exhibits remarkable biological actions, including anti‐inflammation, antiapoptosis, and cytoprotection, at a physiological level. For clinical use without the side effect of tissue hypoxia, which arises from the uncontrolled administration of CO in the human body, CO‐releasing molecules (CORMs) are developed to ensure safe and efficient CO‐delivery. Herein, a syringe‐injectable CO‐releasing peptide hydrogel (COH ) and a corresponding bioadhesive hydrogel patch (COHP ), developed by rational supramolecular chemistry, to enhance the therapeutic efficacy of CO with controllable CO‐release to a specific tissue is report. The injectable COH is prepared by self‐assembly of the CORM‐attached peptides with a gel‐forming diphenylalanine‐derivative, resulting in fibrillar networks and exhibiting prolonged CO‐release compared with CORMs. Furthermore, Ca 2+ ‐chelating and mussel‐derived catechol‐functionalized peptides are introduced to afford a mechanically rigid, bioadhesive COHP that elicits cytoprotective and anti‐inflammatory activities. The supramolecular COHP can be utilized in the efficient CO‐delivery to the site of interest by conformal contacts, making it a promising scaffold for biomedical applications. Abstract : A therapeutic carbon monoxide (CO)‐releasing hydrogel patch is fabricated by self‐assembly of rationally designed peptides. Increase in mechanical strength and adhesive force of hydrogel enables the local CO‐delivery with its sustained release. The hydrogel patch elicits effective cytoprotective and anti‐inflammatory effects on cardiomyocytes by conformally contacting with the desired tissues, resulting in an efficient nanoplatform for a medical gas therapy.